O prurido mediado pelo receptor para o peptídeo liberador de gastrina (GRPR) é dependente da via de sinalização PI3KΎ/Akt - Pereira, Paula Juliana Brizuela de Seadi (2016)
The gastrin-releasing peptide (GRP) and its receptor (GRPR) were recently identified as specific components of pruritus, suggesting an important pharmacological potential for this system; however, the mechanisms underlying GRP/GRPR activity remain undefined. Herein, we evaluated GRPR localization and downstream signaling pathways. Our data show that GRP directly activates small-size capsaicin-sensitive DRG neurons, an effect that translates into transient calcium flux and membrane depolarization. Expression profile revealed that PI3KΎ is downstream of the GRP/GRPR axis, observed by GRP-induced Akt phosphorylation in ex vivo naive mouse spinal cords and in GRPR transiently expressing HEK293 cells. However, ex vivo mouse spinal cord stimulation by GRP failed to induce the activation of MAP-kinases, namely ERK 1/2 and p38. Intrathecal GRP administration led to intense scratching behavior, an effect significantly reduced by either GRPR antagonism or the PI3KΎ inhibition. We assessed whether the GRP/GRPR system is involved in chronic itching using the dry skin model and found that GRPR blockade or PI3KΎ inhibition reversed the scratching. We also found that p-Akt and GRPR are co-expressed in the spinal cord and in DRG neurons from dry skin mice, and that p-Akt levels are increased in these animals, an effect prevented by GRPR blockade. The intradermal injection of GRP also triggers scratching behavior, which was significantly decreased after treatment with PI3KΎ inhibitor. The itching response was also induced by the intrathecal injection of an Akt activator. Altogether, these findings are highly suggestive that GRPR is expressed by the peripheral and central terminals of DRG nociceptive afferents, which transmit itch via the PI3KΎ/Akt pathway.